Combatting institutional corruption: the policy-centered approach - Martinsson, Joel (Crime, law and social change, 2021)
How can institutional corruption be combatted? While recent years have seen a growth in anti-corruption literature, examples of countries rooting out systemic corruption remain few. The lack of success stories has sparked an academic debate about the theoretical foundations of anti-corruption frameworks: primarily between proponents of the principal-agent framework and those seeing systemic corruption as the result of collective-action problems. Through an analysis of current principal-agent and collective action anti-corruption literature, this article adds two additional arguments to the debate: (a) the need to specify what one talks about when talking about systemic corruption and (b) the necessity to move beyond the principal-agent versus collective action frameworks dichotomy towards a policy-centered approach for how to combat institutional corruption. Having outlined how institutional corruption can be seen as one type of systemic corruption, this article shows how a policy-centered approach such as strengthening the appearance standard through an independent public commission can address theoretical mechanisms emphasized in each anti-corruption framework-thus arguing that the frameworks complement rather than rival each other. The article ends by arguing for an anti-corruption discourse acknowledging that a multifaceted problem such as corruption requires multiple frameworks rather than attempts for silver-bullet explanations.